Analisis Faktor Penyebab Bencana Banjir di Kota-Kota Besar Indonesia: Studi Kasus Analisis Banjir Berbasis Literasi - Arvi, Mayfa Dwi; Sibarani, Ruth Masta Yemima; Tanjung, Yul Ifda; Fairuz, Tariza (Indonesian Journal of Emerging Trends in Community Empowerment, 2025)
One of the natural phenomena that threatens human survival is natural disasters. Natural disasters are uncontrolled natural events or occurrences that can cause serious damage to the environment, property, and human life. One of the natural disasters is flooding. Flooding is an event caused by many factors, both natural factors and human factors. The purpose of this study is to determine the various factors that cause flooding in urban areas. The research method used in the study is based on a literature study based on literature studies. From the results obtained from this study, the cause of flooding can occur from 2 factors, namely natural factors and human factors, the natural factors that dominate flooding are high rainfall, the geographical influence of rivers in the upstream and downstream areas, sedimentation. In addition, factors caused by humans are changes in the land surface that become watertight due to permanent development, and a decrease in water catchment areas.